2016
DOI: 10.1161/jaha.115.002468
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss in Obese Patients With Heart Failure

Abstract: Background In heart failure ( HF ), weight loss ( WL ) has been associated with an adverse prognosis whereas obesity has been linked to lower mortality (the obesity paradox). The impact of WL in obese patients with HF is incompletely understood. Our objective was to explore the prevalence of WL and its impact on long‐term mortality, with an emphasis on obese patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 45 publications
2
40
0
2
Order By: Relevance
“…However, weight loss is also associated with a poor prognosis, particularly in those patients who are obese at baseline. 24…”
Section: Discussionmentioning
confidence: 99%
“…However, weight loss is also associated with a poor prognosis, particularly in those patients who are obese at baseline. 24…”
Section: Discussionmentioning
confidence: 99%
“…131 Other studies estimate a prevalence of cardiac cachexia of 5-15% in CHF. 133 Patients with cardiac cachexia show higher rates of atrial fibrillation, 134 possibly contributing to the increased mortality. 4 Cardiac cachexia has a dramatic prognostic impact with an 18 month mortality rate of up to 50%, 132 mortality is particularly high in obese cachectic CHF patients.…”
Section: Transition To Cardiac Cachexiamentioning
confidence: 99%
“…However, in the LIVE trial, liraglutide was associated with an increased risk of adverse cardiac events (including ventricular tachycardia, atrial fibrillation, acute coronary syndrome, and worsening HF; 12 with liraglutide vs. 3 with placebo; P = 0.04). An obesity paradox has been demonstrated among patients with HF, and unexpected weight loss among patients with chronic HF is associated with an increased risk of death 21,22 ; this risk extends to obese patients with HF. Furthermore, HbA1c was significantly reduced in the liraglutide arm compared with placebo (mean difference À0.4%; P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…17 Our results did align with the finding in the LIVE trial that demonstrated that liraglutide treatment was associated with a weight loss of 2.2 ± 3.1 kg compared with placebo (0.0 ± 3.0 kg) (mean difference À2.2 kg; P < 0.0001). 22 Prior analyses have also suggested that weight loss may decrease arterial stiffness 23 and weight gain may be associated with increased ventricular stiffness. 17 Despite the challenges of identifying HF events in a high risk population, 18 concern was raised regarding a possible increase in HF risk among patients with a higher BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation